2014
DOI: 10.1371/journal.pone.0096011
|View full text |Cite
|
Sign up to set email alerts
|

QTL Conferring Fusarium Crown Rot Resistance in the Elite Bread Wheat Variety EGA Wylie

Abstract: Fusarium crown rot (FCR) is one of the most damaging cereal diseases in semi-arid regions worldwide. The genetics of FCR resistance in the bread wheat (Triticum eastivum L.) variety EGA Wylie, the most resistant commercial variety available, was studied by QTL mapping. Three populations of recombinant inbred lines were developed with this elite variety as the resistant parent. Four QTL conferring FCR resistance were detected and resistance alleles of all of them were derived from the resistant parent EGA Wylie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 27 publications
5
35
0
Order By: Relevance
“…; Zheng et al. ). However, it is not clear whether the different FCR severities observed between tall and dwarf genotypes were due to different susceptibility of genotypes with different heights to the same concentration of the pathogen or the shorter genotypes could indeed slow down the development of FCR.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…; Zheng et al. ). However, it is not clear whether the different FCR severities observed between tall and dwarf genotypes were due to different susceptibility of genotypes with different heights to the same concentration of the pathogen or the shorter genotypes could indeed slow down the development of FCR.…”
Section: Discussionmentioning
confidence: 98%
“…; Zheng et al. ). Further studies based on near isogenic lines (NILs) for various reduced height ( Rht ) genes confirmed the initial observation from the use of segregating populations that dwarf isolines indeed showed reduced symptom of the disease in wheat (Liu et al.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Drysdale is an Australian cultivar with superior transpiration efficiency (Condon et al, 2004;Tausz-Posch et al, 2012). SB062 is a breeding line developed in the 'Physiological Wylie has high levels of Fusarium crown rot resistance and black point tolerance (Queensland Wheat Variety Guide, 2014;Zheng et al, 2014). The Australian cultivar Westonia was selected for acid soil tolerance, and tolerance to manganese and aluminium toxicities in soil (Tang et al, 2003;Khabaz-Saberi et al, 2010).…”
Section: Plant Materialsmentioning
confidence: 99%